Boiling Time-Dependent Studies on the Total Flavonoids Content and Antioxidant Activities in Dendrophtoe Petandra (L.) Miq. - Susilowati Susilowati; Alip Desi (Indonesian Journal of Global Health Research, 2022)
Boiling time effect on total flavonoid content and antioxidant activity of Dendrophthoe petandra leaves were studied. D. petandra is a parasite plant that is widely used on Indonesian people for traditional medicine with boiling techniques. The dried leaves were boiled in water for 5, 10 and 15 minutes, and quantitative analysis was performed from each boiled water. Total flavonoid levels were analyzed using UV/Visible Spectrophotometry as quercetin equivalent (QE) and antioxidant activity using FRAP (Ferric Reducing Antioxidant Power) as ascorbic acid equivalent (AAE). The total flavonoid levels and antioxidant activity showed a considerable change. The boiled water of D. petandra leaves for 10 minutes showed the highest level of total flavonoid content (9.0098 ± 0.0340 ppm QE) and antioxidant activity (30.6792 ± 0,0270 ppm AAE), whereas the content of total flavonoids were 7.2350 ± 0.0299 ppm QE and antioxidant activity were 23.9533 ± 0,0486 ppm AAE showed the lowest results boiling for 15-minute. Total flavonoid and antioxidant activity of boiling time for 5 minutes increases to 10 minutes and then decreased at 15-minute. Therefore, it is improper to boil the D. petandra leaves more than 10 minutes.